Active Separation Control on Thick Wind Turbine Airfoils by Means of Steady and Unsteady Blowing. Issue 7 (20th May 2019) - Kankatala, Prabhu; Bangga, Galih
Abstract: Investigations of active flow control (AFC) using steady and unsteady sinusoidal blowing jet on thick wind turbine airfoils are performed. The focus is on improving the performance of the DU 00‐W2‐401 airfoil through parametric study and to discuss the effectiveness of optimized configuration. The unsteady Reynolds‐Averaged Navier‐Stokes (URANS) and delayed‐detached eddy simulation (DDES) approaches are employed with controlled flow conditions. The turbulent statistics produced from the flow development through DDES approach is used to analyze the flow. Unsteadiness associated with the massively separated flows is investigated and a strategy is charted to perform the parametric study efficiently and profitably. The interdependencies of the blowing jet parameters are investigated. The studies address airfoil performance improvement through the nonzero‐net‐mass‐flux (NZNMF) slot blowing at different positions, angles of blowing, flow rates, forcing frequencies, and amplitudes of the blowing jet. The computed time‐averaged aerodynamic force coefficients, pressure distributions, and time‐resolved flow field contours are utilized to analyze the flow conditions at various configurations. A final optimum parametric configuration is found out, which results in improved aerodynamic performance. The optimum configuration is tested for airfoil sections of a 10 MW generic turbine at actual operating inflow conditions and ascertained that it is effective. Abstract : Flow separation on thick wind turbine airfoils can be effectively delayed using actively controlled blowing jet. The phenomena are driven by the injected momentum and unsteady disturbance on the boundary layer. Studies based on the nonzero‐net‐mass‐flux (NZNMF) slot blowing are carried out numerically using URANS and DDES. Systematic guidelines for the optimization process are given in this work.